Derangement of protein S and C4b-binding protein levels as acquired thrombophilia in HIV-infected adult Nigerians - Fatai O. Bello; Alani S. Akanmu; Titilope A. Adeyemo; Bukunmi M. Idowu; Prosper Okonkwo; Phyllis J. Kanki (AOSIS, 2021)
Background: HIV is a chronic inflammatory state with the production of many acute-phase-reactant proteins. Some of these proteins have procoagulant activities that predispose HIV-infected patients to thrombosis. Objectives: The aim of the study was to evaluate the effects of HIV infection on the serum levels of C4b-binding protein (C4BP) and protein S as markers of predisposition to thrombosis in HIV-infected adults. Methods: The study population comprised of 61 HIV-infected adults on antiretroviral treatment (ART) who had achieved virological suppression, 58 HIV-infected adults not yet on ART and 59 HIV-negative healthy controls. The serum levels of free protein S, C4BP and the euglobulin clot lysis time (ECLT) were determined. Results: The mean plasma-free protein S level of HIV-infected patients on ART (86.9% ± 25.8%) was significantly higher than that of treatment-naïve HIV-infected patients (75.7% ± 27.3%) (p = 0.005). Conversely, there was no statistically significant difference between the protein S levels of the HIV-infected subjects on ART (86.9% ± 25.8%) and those of the controls (94.9% ± 7.9%) (p = 0.119). The mean C4BP was significantly higher in the treatment-naïve HIV-infected subjects (36.7 ± 1.7 ng/dL) than that in those on ART (30.7 ± 2.6 ng/dL) and that in the controls (22.4 ± 2.4 ng/dL) (p 0.0001). Protein S deficiency was more prevalent among the subjects with elevated C4BP (p = 0.023). The mean ECLT was significantly more prolonged in the treatment-naïve HIV-infected subjects (241.9 ± 34.7 s) than controls (189.5 ± 40.7 s) (p  0.0001). Conclusion: HIV infection causes elevated levels of C4BP and diminishes the serum levels of free protein S. We infer that the risk of thrombosis (as measured by these biomarkers) decreases with the use of antiretroviral drugs.